Modelagem Matemática na Educação Matemática: Possibilidades de avanços para uma nova racionalidade no processo de ensino e aprendizagem da matemática no Ensino Fundamental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The practices approached from Modeling, in a Mathematics Education concept, have been gaining visibility as a teaching methodology for Mathematics. In view of its interdisciplinary scientific construct, which in addition to Mathematics involves areas of Education, Philosophy, Mother Tongue that it inherits from Mathematics Education, it presents great possibilities to enrich the teaching process with a view to learning. Working with Mathematical Modeling makes it possible to develop other capacities, in addition to those exclusively linked to mathematical concepts. In this perspective, the present research intends to contribute to the teaching of mathematics, showing, through practices with Mathematical Modeling assumed by the conception adopted by Burak (2002), from the analysis of dissertations, elements that contribute to the construction of a new rationality in the process of teaching and learning mathematics, especially in Elementary School. Seeking to answer: What is shown of the practices with Mathematical Modeling, in a conception of Mathematics Education, from the analysis of dissertations in Elementary School, capable of instituting elements for a new rationality in the teaching and learning process? It is a bibliographic research and the material of analysis consists of 3 (three) dissertations that involve 9 (nine) practices with Mathematical Modeling developed in the context of Elementary School, by the conception of Mathematics Education, with the objective of identifying actions, approaches and procedures that can characterize a new rationality in the teaching and learning process. Research and data processing are guided by the perspective of Bogdan and Biklen (1994). The elements capable of contributing to the construction of a new rationality, perceived and constant in the collected data, were treated in the perspective of the principles of Complex Thinking proposed by Morin (2007). The principles punctuated as dialogic, retroactive and recursive circuit, systemic, reintroduction, hologrammatic and self-eco-organization, were present in several moments in the stages of Mathematical Modeling in the analyzed practices. In this new rationality, some elements are present, namely: the interaction, the freedom provided, the present dialogue, the gradual development of autonomy. Therefore, it shows that in all the stages of Choosing a theme, Exploratory research, Surveying problems, Solving problems and the Critical stage of solutions are present in the principles of complex thinking, thus contributing to punctuate elements for the construction of a new rationality.
Keywords: Modelagem Matemática; Racionalidade; Educação Matemática; Ensino Fundamental; Mathematical Modeling; Rationality; Mathematics Education; Elementary School; CNPQ::CIENCIAS EXATAS E DA TERRA